2014
DOI: 10.3171/2014.6.jns131673
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of diffusion tensor tractography and intraoperative macrostimulation during deep brain stimulation for Parkinson disease

Abstract: Introduction Diffusion-MRI is a rapidly evolving research field that has produced a wealth of algorithms for the analysis of white matter fibre architecture and disorders in the brain. Camino is a free, open-source toolkit designed to make a selection of this technology available and convenient to use for the diffusion MRI research community. Camino implements a data processing pipeline, which allows for easy scripting and flexible integration with other software. This abstract summarises the features of Camin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…We were recently able to investigate the accuracy of the DTI-FT approach for DBS and despite the results of other groups [20], concluded that the accuracy of the approach allows for direct targeting in DBS surgery [5, 6]. Other groups are now starting to use probabilistic tracking algorithms to resolve problems of inferior resolution, kissing, branching, and crossing fibers and the problem of deformed fibers [15].…”
Section: Discussionmentioning
confidence: 99%
“…We were recently able to investigate the accuracy of the DTI-FT approach for DBS and despite the results of other groups [20], concluded that the accuracy of the approach allows for direct targeting in DBS surgery [5, 6]. Other groups are now starting to use probabilistic tracking algorithms to resolve problems of inferior resolution, kissing, branching, and crossing fibers and the problem of deformed fibers [15].…”
Section: Discussionmentioning
confidence: 99%
“…5 Other groups have tried to approach the accuracy level of DTI in clinical DBS procedures and have come to the conclusion that the use of DBS surgery with this technology cannot be advised. 31 While this conclusion might be true, in our opinion, these authors based their results on imaging data, software use, and a study setup that was not geared to looking at the specific questions asked. 32 Therefore, a specific approach designed to look at this problem, albeit still in a clinical setting, appeared appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Biophysical models like the volume theoretically activated by the DBS are some well-described techniques to prevent this effect [27,28]. With contradictory results [29][30][31], these models have been combined with the use of tractography to compute the overlap between the volume of tissue theoretically activated and the pyramidal tract. Those works have opened the path for the hotly anticipated directional leads that might widen the therapeutic window and be beneficial for the patients [32][33][34].…”
Section: Discussionmentioning
confidence: 99%